PHYSICAL ACTIVITY, SCREEN TIME, NUTRITIONAL STATUS AND SLEEP IN ADOLESCENTS IN NORTHEAST BRAZIL - Souza Neto,João Miguel de (2021)
ABSTRACT Objective: To verify the prevalence of sleep quality and duration and its association with the level of physical activity, screen time and nutritional status in adolescents. Methods: This is a cross-sectional study with 1,432 adolescents (53.1%, female), ten to 14 years old (12.0±1.0 year) from public schools in Joao Pessoa, Northeast Brazil. Physical activity (≥300 vs. <300 minutes/week), screen time (≤2 vs. >2 h/day) and duration (<8 vs. ≥8 h/day) and perception of sleep quality (negative vs. positive perception) were measured by questionnaire. Nutritional status was assessed by body mass index (low weight / normal weight vs. overweight / obesity). Binary logistic regression was used to analyze association between variables, considering different aggregation of negative factors. Results: The prevalence of insufficient duration and negative perception of sleep quality was 12.6% (95%CI 10.9-14.4) and 21.0% (95%CI 18.9-23.1), respectively. There was a linear trend in the chance of the adolescents to present insufficient duration of sleep as a result of simultaneous negative factors (physical inactivity, excessive screen time, being overweight) (OR=4.31; 95%CI 1.50-12.48). Conclusions: Adolescents exposed simultaneously to low levels of physical activity, excessive screen time and overweight had a lower sleep duration.